Optimal Control for Networked Control Systems with Markovian Packet Losses - Xiao Han; Zhijian Ji; Qingyuan Qi (Complexity)
This paper is concerned with the optimal output feedback control problem for networked control systems (NCSs) with Markovian packet losses. In this paper, the packet losses occur both between the sensor and controller and between the controller and actuator. Moreover, the packet loss channels are described with two-state Markov chains. Since the precise state information cannot be obtained, thus an optimal recursive estimator is designed. Furthermore, by adopting the dynamic programming approach, we derive the optimal output feedback control, which is based on the solution to a given modified Riccati equation. The obtained results can be seen as an important implementation of the control theory for NCSs with unreliable communication channels.